Literature and skepticism - Oyarzún R., Pablo 1950- (Albany State University of New York Press, 2022)
"Examines the skeptical foundations of literature in order to reassess the status of fiction"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Skepticism in literature; Fiction -- History and criticism; Electronic books